Preaching at the Crossroads : How the World-and Our Preaching-Is Changing - Lose, David J. (Book collections on Project MUSE., 2013)
"Postmodernism. Secularism. Pluralism. These are the words often used to describe the tumultuous changes that have affected our culture and our churches. But what do they really mean? More importantly, what challenges and opportunities do they provide today's preachers? David Lose takes preachers on a tour of the major cultural influences of the last century, explaining how they have contributed to the diminishment of the church and exploring how they also offer opportunities to cultivate a more vibrant and relevant faith in the twenty-first century. Filled with lucid analysis and practical suggestions, Preaching at the Crossroads invites preachers to reclaim the art of preaching the timeless Gospel in a timely and compelling manner"--